Peningkatan Hasil Belajar Bahasa Inggris melalui Penerapan Metode Demonstrasi Masa Pandemi Covid 19 pada Siswa Kelas IX-A SMP Negeri 3 Masbagik Tahun Pelajaran 2020/2021 - Fitriah, Fitriah (Lembaga Yasin AlSys, 2021)
This Classroom Action Research was conducted by applying the demonstration method to improve English learning outcomes for grade IX-A students of SMPN 3 Masbagik. This Classroom Action Research (CAR) was conducted with the aim of knowing the improvement of English learning outcomes through the application of the demonstration method to class IX.9 students of SMPN 1 Masbagik in the 2020/2021 school year. This Classroom Action Research (CAR) was carried out in stages 2 cycles, and from the results of the actions that have been carried out it has been proven to improve student learning outcomes both in terms of classical student learning completeness, namely in the first cycle of 72%, it can increase to 86% in the second cycle. means that there is an increase of 14% and in terms of the average value of the evaluation results there is also an increase.